The chemokine receptor CCR9 is required for the T cell-mediated regulation of chronic ileitis in mice - Wermers, Joshua D. (2011)
BACKGROUND & AIMS: A balance between effector and regulatory (Treg) T-cell responses is required to maintain intestinal homeostasis. To regulate immunity, T cells migrate to the intestine using a combination of adhesion molecules and chemokine receptors. However, it is not known whether the migration pathways of effector cells and Tregs are distinct or shared. We sought to determine whether interaction between the chemokine CCR9 and its receptor, CCL25, allows effectors or Tregs to localize to chronically inflamed small intestine. METHODS: Using a mouse model that develops Crohn's-like ileitis (TNFΔARE mice) we examined the role of CCL25–CCR9 interactions for effector and Treg traffic using flow cytometry, quantitative reverse transcription PCR, immunohistochemistry, immunoneutralization, and proliferation analyses. RESULTS: In TNFΔARE mice, expression of CCL25 and the frequency of CCR9-expressing lymphocytes increased during late-stage disease. In the absence of CCR9, TNFΔARE mice developed exacerbated disease, compared with their CCR9-sufficient counterparts, which coincided with a deficiency of CD4(+)/CD25(+)/FoxP3(+) and CD8(+)/CD103(+) Tregs within the intestinal lamina propria and mesenteric lymph nodes. Furthermore, the CD8(+)/CCR9(+) subset decreased the proliferation of CD4(+) T cells in vitro. Administration of a monoclonal antibody against CCR9 to TNFΔARE mice exacerbated ileitis in vivo, confirming the regulatory role of CD8(+)/CCR9(+) cells. CONCLUSIONS: Signaling of the chemokine CCL25 through its receptor CCR9 induces Tregs to migrate to the intestine. These findings raise concerns about the development of reagents to disrupt this pathway for the treatment of patients with Crohn's disease.